Hubungan Tingkat Kecemasan Dengan Kualitas Tidur Ibu Hamil Trimester III Menghadapi Persalinan Di Wilayah Kerja Puskesmas Sawah Lebar Kota Bengkulu Tahun 2025 - Zakiah Septi Ardita; Yesi Putri; Murwati Murwati (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Indonesia still faces various problems in the health of pregnant women, one of which is anxiety frequently experienced especially in the third trimester approaching childbirth. Physical, psychological, and hormonal changes during pregnancy can increase feelings of fear, worry, and discomfort that affect the condition of pregnant women. Anxiety experienced by pregnant women can affect various aspects of health, one of which is sleep quality. Sleep disturbances that occur can disrupt daily activities and reduce the comfort and well-being of pregnant women. This study aims to determine the relationship between anxiety levels and sleep quality of pregnant women in the third trimester facing childbirth in the working area of Sawah Lebar Health Center, Bengkulu City, 2025. This study used a quantitative design with a cross-sectional approach. The population and sample in this study were all pregnant women in the third trimester totaling 32 respondents using total sampling technique. The instruments used were the Pregnancy Related Anxiety Questionnaire-Revised (PRAQ-R2) and to measure the level of anxiety the Pittsburgh Sleep Quality Index (PSQI) was used to assess sleep quality. The results showed that most pregnant women in the third trimester experienced severe anxiety levels totaling 23 respondents (71.9%) and most respondents had poor sleep quality totaling 17 respondents (53.1%). Bivariate analysis results showed there was a relationship between anxiety levels and sleep quality of pregnant women in the third trimester with a p-value =0.001 (< 0.05), which means the higher the level of anxiety the worse the sleep quality of pregnant women. It is expected that the health workers can increase efforts in education and nursing interventions to help reduce anxiety levels of pregnant women in the third trimester so that sleep quality can be well maintained. In addition, pregnant women are expected to be able to utilize health services optimally as part of preparation for facing childbirth.